Case Analysis On Advanced Micro Devices Inc.(AMD) - Ahmad, Normarina (2003)
AMD regards itself as a global supplier of integrated circuits for the personal and networked computer markets. Its products are microprocessors, Flash memory devices, and integrated circuits for communications and networking applications.